DENSITIES OF DEHYDROGENATED POLYMER SOLUTIONS IN DIMETHYLSULFOXIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
Densities of dehydrogenated polymer (DHP) solutions in DMSO have been investigated in the temperature range 20–70°C. It has been shown that the density of the solution with a certain concentration of DHP in DMSO increases progressively with time tending to a constant value, whereas in the case of diluting the density of the solution varies, passing through the maximum point.
Keywords: lignin, dehydrogenated polymer, solution density, structural changes, dimethylsulfoxide